(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This scientific article delves into the imperative need for cultivating ecological culture among students of pedagogical universities. In an era marked by pressing environmental challenges, the role of educators in nurturing environmentally conscious individuals is paramount. This article explores the significance of integrating ecological education into the curriculum, fostering a deep-seated respect for nature, and instilling sustainable practices among future educators. Various strategies, challenges, and outcomes of developing ecological culture among students are discussed, emphasizing the pivotal role of pedagogical institutions in shaping environmentally responsible citizens.